Perancangan Reversible Office Wear Sebagai Penunjang Lifestyle Wanita Karir Untuk Brand Audhea - Audhea Adistya Sudaryoto; Enrico - (Universitas Ciputra Surabaya, 2017)
Brand Audhea collection is created to provide business attire for career women who have hectic schedule at both home and office. They have limited time in making decision which clothes they should wear due to many choices of clothes in their closet. Therefore, with the existence of brand Audhea, career women would have more option to choose work outfits that look modern yet comfortable and also versatile at the same time because of its reversible style. Using interview as a method of qualitative research by interviewing career woman as extreme user and fashion expert as expert user , as well as doing research through various sources, the final result are 5 sets of office wear which can be worn both the outside or the inside with comfortable fabric and modern design along with lookbook and corporate identity of brand Audhea.